Comparison in a rat thigh abscess model of imipenem, meropenem and cefoperazone-sulbactam against Acinetobacter baumannii strains in terms of bactericidal efficacy and resistance selection - Gundes Sibel; Budak Fatma; Oz Sarpkaya; Okay Erdem; Karadenizli Aynur; Fetiye Kolayli; Vahaboglu Haluk (BMC, 2004)
Abstract Background We compared imipenem, meropenem and cefoperazone-sulbactam against hospital originated A. baumannii strains in terms of bactericidal efficacy and selection of resistant mutants during treatment in a rat thigh abscess model. Methods A total of 18 strains were inoculated in 54 animals (one strain for three animals). Randomly selected 10 among these 18 strains were inoculated in another 10 rats as the control group. Imipenem, meropenem and cefoperazone-sulbactam were the antibiotics compared. After four days of treatment, Wistar albino rats (200 to 250 g) were sacrificed and the abscess materials were processed for mean colony counts and for the presence of resistant mutants. Results The mean CFUs per gram (mean ± (std. deviation) [×104]) of the abscess were: 9,14 (25,24), 2,11 (3,78), 1,20 (1,70) in the imipenem (n = 17), meropenem (n = 18) and cefoperazone-sulbactam (n = 17) groups, respectively. The differences were not significant. On the other hand, no resistant mutant was detected in abscess materials. Conclusion This study indicated; first, cefoperazone-sulbactam is comparable to carbapenems in bactericidal efficacy in this particular abscess model and second, emergence of resistance due to spontaneous mutations is not at least a frequent phenomenon among A. baumannii.